FAKTOR RISIKO KEJADIAN BALITA DENGAN BERAT BADAN DI BAWAH GARIS MERAH (BGM) DI DESA PANCAROBA KECAMATAN AMBAWANG KABUPATEN KUBU RAYA TAHUN 2015 - Alamsyah, Dedi; Rohmady, Roby (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Pontianak, 2016)
Weight Under the Red Line (BGM) ie when the weight of the baby or toddler is under the red line on the KMS (Card Towards Healthy). Based on secondary data obtained in the village Pancaroba 8 toddlers below the red lines of the existing total of 211 children (instead of D / S). From the above data it is known that there are parents who have parenting poor nutrition and poor knowledge The aim in this study was to determine the